PENDIDIKAN SEKSUALITAS: Upaya Pencegahan Penyimpangan Perilaku Seksual Remaja Masa Kini - Panjaitan, Firman (BONAFIDE: Jurnal Teologi dan Pendidikan Kristen, 2024)
Sexuality education is necessary for adolescents, especially from their parents. This is because adolescents experience rapid physical and sexual development, and they need guidance to gain a correct understanding of sexuality. Parents are the most responsible figures for providing this understanding. This study aims to emphasize that sexuality education is not a taboo subject and that parents must provide it to prevent their teenage children from engaging in sexual misconduct. The study uses a qualitative method, specifically a literature review. The findings and recommendations of this study confirm that parents are not only responsible for providing sexuality education to their adolescent children, but it is also an absolute necessity. Through proper, complete, and comprehensive sexuality education from parents, teenagers can control themselves and avoid sexual misconduct.